2010
DOI: 10.1375/ajgc.20.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-Victimisation: The Association Between Help-Seeking Behaviours and Self-Reported Emotional Symptoms in Australia and Austria

Abstract: Many young people who are bullied do not tell anyone. School staff therefore are often unaware of which students are being victimised and when to provide support or assistance. A critical strategy to overcome this problem is to encourage victimised students to seek help and report this bullying. This study aims to examine the relationship between help-seeking behaviours and self-reported emotional symptoms in young people from Australia (n = 5959; M age = 12.36 years, SD = 1.46 years) and Austria (n = 1530; M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 34 publications
4
51
1
6
Order By: Relevance
“…It may be that the persistent and pervasive nature of cybervictimisation may lead to feelings of hopelessness, which are associated with suicidal behaviours in adolescents [60]. Students who are cybervictimised are less likely to report and seek help than those victimised by more traditional means [61,62], therefore it is important for staff to encourage help-seeking in relation to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the persistent and pervasive nature of cybervictimisation may lead to feelings of hopelessness, which are associated with suicidal behaviours in adolescents [60]. Students who are cybervictimised are less likely to report and seek help than those victimised by more traditional means [61,62], therefore it is important for staff to encourage help-seeking in relation to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…This figure for cyber victims had risen to 19% by middle school and 26% in the final years. Price and Dalgleish's study [27] of 548 Australians found that cyber bullying occurred mostly in the period of transition from primary to secondary school. Their participants experienced cyber bullying at multiple ages when growing up, with the range being from 10 to 16 years.…”
Section: Age and Gender Factors In Cyber Bullyingmentioning
confidence: 99%
“…Australian cyber bullies used mostly text messages, followed closely by chat rooms and then by electronic mailing [27]. Price and Dalgleish [28] also surveyed Australian students, with email (21%), online chatrooms (20%), social networking sites (20 %), mobile phones (19% ) and internet website (8%) used for cyber bullying in the sample of 548 participants.…”
Section: Use Of Technologies For Cyber Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Female victims of cyberbullying are more likely to have emotional symptoms than male victims. However, females tend to ask for help more than males (Dooley et al, Cross and Spiel, 2010).…”
Section: Its Effects On Victimsmentioning
confidence: 99%